"Sticky molecules" on rock surface might play an important role in formation damage due to asphaltene deposition. (1st October 2020) - Zeng, Huang; Tessarolo, Nathalia; Gonzalez, Doris; Gramin, Pavel; Wicking, Chrissie; Pietrobon, Marney
Graphical abstract: Highlights: The organics on the surface of reservoir rock have been extracted and characterized. The surface of the intact oil-zone reservoir rock is covered with a layer of special "sticky molecules". These "sticky molecules" are also found on the surface of the water-zone core which has been aged at reservoir conditions. Asphaltene molecules are found on the surface of the aged water-zone core in which asphaltene deposition has been induced. The novel "special molecules" might act as "double-sided tape" to promote the deposition of the asphaltene on rock surface. Abstract: During the production of oil asphaltenes might be deposited onto the near-wellbore area and hinder oil production. In the present study, we have extracted and characterized the organics on the surface of three reservoir rock plugs including (1) a plug from water-zone of a formation; (2) a plug from oil-zone of the same formation; (3) a water-zone plug which has been aged using the crude oil produced from the same formation in the presence of formation brine at reservoir conditions, and then the pressure has been depleted to just below asphaltene onset pressure (AOP) to introduce asphaltene deposition. The key conclusions are as followed. (1) the composition of the organics on the surface of reservoir rock and aged rock are significantly different from that of the crude oil, and these organics are likely distributed in a layered structure; (2) More importantly, it is striking to find that the organics in the first layer (bottom layer) of the reservoir rock and the aged rock are dominated with characteristic "sticky" molecules which, to our best knowledge, have not been reported in literature regarding asphaltene deposition. These special organics have multiple polar functional groups which might allow them to act as the "anchors" to bind the asphaltenes on the rock surface. This finding provides a new mechanism for the asphaltene deposition and might help to understand why asphaltenes are "sticky" when they are deposited. It is envisioned that this result could lead to new strategies to control and remediate asphaltene deposition issues.